The Effect Of Workload And Work Discipline On The Performance Of Bank Mandiri Employees In Tais Market - Yella Cantika; Neri Susanti; Andriyani Prawitasari (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2026)
The purpose of this study is to simultaneously determine the impact of workload and work discipline on the performance of Bank Mandiri Pasar Tais employees. This study uses quantitative associative research with a population of 32 employees and employs saturated sampling techniques. The research data was collected through a questionnaire with a Likert scale, then analyzed using multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results of the study show that: The workload variable has a positive and significant effect on employee performance, as does the work discipline variable, which also has a positive and significant effect on employee performance. Simultaneously, both variables have a significant effect on employee performance with a t-value of 11.758, which is greater than the t-table value of 3.340 and a significance value of 0.000, which is less than 0.05. The R² value of 0.448 indicates that workload and work discipline contribute 44.8% to the variation in employee performance, while the remaining 55.2% is influenced by other factors outside this study. Based on the results of multiple linear regression, the equation Y = 3.820 + 0.500X₁ + 0.371X₂ + ε was obtained. The results of the study and the Workload hypothesis show that it can be concluded that the better the management of workload and the implementation of work discipline, the higher the performance of Bank Mandiri Pasar Tais employees will be.